INDEX OF THE ARTICLES PUBLISHED IN THE JOURNAL "RATIONAL PHARMACOTHERAPY IN CARDIOLOGY" IN 2009 (Столичная издательская компания, 2016)
Index of the articles published in the journal "Rational Pharmacotherapy in Cardiology" in 2009.